Evaluation of digital teaching materials in the Be-Smart course on Indonesian Language and Literature Learning Strategy - Mei Purwantini; Firstya Evi Dianastiti; Fitria Wiyarti Nindyaningrum; Aptia Ardiasri (Jurnal Bebasan, 2025)
This study aims to evaluate the digital teaching materials used in  the Be-Smart  UNY LMS course on Indonesian Language and Literature Learning Strategy based on students' perceptions and experiences. This study uses the Kirkpatrick evaluation model which consists of four levels, namely (1) reaction, (2) learning, (3) behavior, and (4) results. However, this study evaluates at two levels, namely (a) reaction evaluation and (b) learning evaluation. This research is equipped with a mix-method research approach, namely quantitative to find out learning outcomes and qualitative to find out the respondents' experience. The selection of this research method aims to evaluate the Indonesian Language and Literature Learning Strategy lecture using digital teaching materials integrated in  the Be-Smart LMS based on student experience. Data collection in this study was by collecting data from the results of the questionnaire, namely distributing questionnaires through Google Form to get responses from students to the use  of the Be-Smart LMS for students in the Indonesian Language and Literature Learning Strategy course. The overall results of the responses of most students agreed and even strongly agreed that  the Be-Smart page: (a) is easy to access with a score of 48.3%, (b) makes it easier to administer assignments with a score of 44.8%, and the assessment of features in Be-Smart is in accordance with learning needs with a score of 51.7%, as well as  the Be-Smart pageeasily accessible using mobile devices with a score of 62.1%. The results of this evaluation conclude that the digital teaching materials and features on the Be-Smart  page are very easy to apply through mobile devices so as to support the learning of the Indonesian Language and Literature Learning Strategy course offline and online.